Measuring Financial Barriers Among East African Community Countries - Wang, Yi David (IMF Working Papers; Working Paper ;, 2010)
This paper seeks to quantify existing financial barriers among East African Community (EAC) member countries based on analysis of each member country's foreign exchange market. The primary contribution of this paper is the generation of an aggregate measure of financial barriers for the three relatively more advanced members (Kenya, Uganda, and Tanzania) using forward foreign exchange and interbank interest rate data. Its empirical results, which are corroborated by other evidence such as the levels of development of the financial markets and restrictions on capital flows, suggest that Kenya is the EAC's most financially open country, followed by Uganda, and then Tanzania. The fact that the three countries exhibit different degrees of financial openness suggests that financial integration in the EAC region has a way to go.